Design parameters of rainwater harvesting system for selected mosques in Perak towards water saving/ Kazrena Nalia Mat Daud - Mat Daud, Kazrena Nalia (2022)
The function of Rainwater Harvesting System (RWHS) have been expanded tremendously throughout the years with the latest equipment and current technology. Multiple buildings, such as government buildings and others have step up to start implementing this method. Previous studies also have proven that rainwater collected can be used for non-potable and potable water. Nevertheless, the current RWHS design guidelines and practice in Malaysia regarding implementation on other public buildings, particularly religious buildings; buildings that highly involve with large amount of water usage and supply, are not being highlighted. With the addition of water shortage crisis that hit majority parts of the world, a proper solutions is needed to overcome this problem. This research is intend to propose the design parameter of rainwater harvesting system at selected mosques. Hence, the objectives of this study are to determine the general design parameters for RWHS, identifying the significant design parameters of RWHS at mosques, and to propose the specific design parameters of RWHS on mosque towards water savings.